Polarity transitions during neurogenesis and germinal zone exit in the developing central nervous system - Singh, Shalini; Solecki, David J. (Frontiers in Cellular Neuroscience, 2015)
During neural development, billions of neurons differentiate, polarize, migrate and form synapses in a precisely choreographed sequence. These precise developmental events are accompanied by discreet transitions in cellular polarity. While radial glial neural stem cells are highly polarized, transiently amplifying neural progenitors are less polarized after delaminating from their parental stem cell. Moreover, preceding their radial migration to a final laminar position neural progenitors re-adopt a polarized morphology before they embarking on their journey along a glial guide to the destination where they will fully mature. In this review, we will compare and contrast the key polarity transitions of cells derived from a neuroepithelium to the well-characterized polarity transitions that occur in true epithelia. We will highlight recent advances in the field that shows that neuronal progenitor delamination from germinal zone niche shares similarities to an epithelial-mesenchymal transition. Moreover, studies in the cerebellum suggest the acquisition of radial migration and polarity in transiently amplifying neural progenitors share similarities to mesenchymal-epithelial transitions. Where applicable, we will compare and contrast the precise molecular mechanisms used by epithelial cells and neuronal progenitors to control plasticity in cell polarity during their distinct developmental programs.